Reforming Ottoman governance - Andıç, Fuat. (Piscataway, NJ)
xiv, 171 sayfa
Keywords: “The book is the history of reform attempts in the Ottoman Empire and the internal and external difficulties in implementing them. Imperialist aggression towards the Empire and bloody janissary revolts hampered the reforms, and although some successes in governance were achieved, there were many failures, and these contributed to the demise of the Empire at the end of the First World War“ -- Yayıncı.